Formative Versus Reflective Indicators in Organizational Measure Development: A Comparison and Empirical Illustration - Diamantopoulos, Adamantios; Siguaw, Judy A. (British journal of management, 2006)
A comparison is undertaken between scale development and index construction procedures to trace the implications of adopting a reflective versus formative perspective when creating multi‐item measures for organizational research. Focusing on export coordination as an illustrative construct of interest, the results show that the choice of measurement perspective impacts on the content, parsimony and criterion validity of the derived coordination measures. Implications for practising researchers seeking to develop multi‐item measures of organizational constructs are considered.